Investigation of Formation Control Approaches Considering the Ability of a Mobile Robot - Hannes Wind; Oliver Sawodny; Thomas Br•aunl (Institute of Advanced Engineering and Science, 2018)
This work investigates and compares various formation control approaches for mobile robots. A comprehensive literature review was conducted, with particular focus on the approaches' applicability to be implemented on real mobile robots with limited hard and software capabilities. A realistic model of mobile robots is introduced and its parameters are identi ed with measurements from actual mo-bile robots. Later on, the model is extended and used within simulation studies of the various investigated approaches. A collision avoidance controller based on a formation controller is proposed and simulations are carried out. Experiments on real mobile robots are conducted for two formation controllers and for the pro-posed collision avoidance controller. It is shown that if the requirements resulting from the simulation studies are satis ed, an implementation on the real robots is possible.